Pengetahuan Dan Kesiapsiagaan Siswa Dalam Menghadapi Bencana Gempa Bumi Di SMK Muhammadiyah 2 Klaten Utara - Puspitaningrum, Ardiana, Drs. Muhammad Musiyam, M.TP (2016)
This research aimed to known the : 1) the knowledge of students of class X to the earthquake in SMK Muhammadiyah 2 North Klaten, 2) the level of preparedness of stuudents of class X to the disaster earthquake in SMK Muhammadiyah 2 North Klaten, 3) relationsship between knowledge and preparedness in facing disaster earthquake in SMK Muhammadiyah 2 North Klaten. Populatio used in the research is 36 students teams mitigation and 235 students not follow teams mitigations. Sampl the research is class X a number of 32 Students each populations.technical data collections is questionsnaire, observation, and document. Data analisis used correlation Sperman and Kendall. Conclutions in the research that is overall knowledge students have teams mitigations and students not follow teams mitigatios included in goodcategory. Overall readiness owned teams mitigations and studend which not follow teams mitigation included in the category of high achievement. There is a relationship between knowledge and preparedness of students in facting earthquake in SMK Muhammadiyah 2 North Klaten. Keyword : Knowledge, Preparedness, Earthquake